ANALISIS PENGARUH TEMPERATUR HUMANITY INDEKS TERHADAP AKTIVITAS UMKM DI JALAN PURA DEMAK, KOTA DENPASAR - amin; Bela, Riyani; Husnayaen, Husnayaen; Pratama, Adrian; Anhar, Alfian (Jurnal Penelitian Multidisiplin, 2023)
The Jalan Pura Demak area in Denpasar City is a location that has great potential for developing Micro, Small and Medium Enterprises (MSMEs). MSMEs have a strategic role in the local economy, contributing to job creation, economic growth and poverty alleviation. However, the success of MSMEs is very dependent on factors that influence the level of comfort. This research aims to analyze the comfort level of temperature and humidity and its impact on the activities of Micro, Small and Medium Enterprises (MSMEs) on Jalan Pura Demak, Denpasar. The research method used is measuring temperature and humidity and calculating the Temperature Humanity Index. Apart from that, this research also used a questionnaire instrument given to MSME owners who were active in the area. Data analysis was carried out using quantitative descriptive statistical techniques. The research results show that the Temperature Humanity Index at each point is not much different. From the three points of temperature and humidity measurement results, it can be seen that the Humanity Index Temperature at point I (SPBU) on the first day was 21.0 (comfortable), on the second day 24.8 (comfortable), and on the third day 24.8 (comfortable). At point II (Tea Poci), for the first day it was 24.8 (comfortable), for the second day it was 25.6 (medium), for the third day it was 25.6 (medium), while at point III (Circle K) on the first day it was 24, 6 (comfortable), second day 24.8 (comfortable) and third day 24.8). Meanwhile, regarding the value of public perception regarding the level of comfort, around 69% of MSME players still feel safe in their MSME area. This percentage of public perception is correlated with the Temperature Humanity Index at each temperature and humidity measurement point. Thus, it can be concluded that the Jalan Pura Demak route in Denpasar City is not yet in the uncomfortable category for MSMEs